Glass fiber reinforced adhesive tape and preparation method thereof

By using a combination of polypropylene, SEBS and β-shaped nucleating agents and carbon nanomodified glass fibers in glass fiber tape, the problem of insufficient toughness of existing tapes is solved, significantly improving its impact strength and toughness, and improving the Protection effect and safety performance in impact scenarios.

CN119220191AInactive Publication Date: 2024-12-31济宁迅大管道防腐材料有限公司
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411411917.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-11
Publication Date
2024-12-31
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Existing glass fiber tapes are not tough enough when impacted and are prone to breaking, resulting in reduced protection effect and safety performance.

Method used

Polypropylene (PP) is used as the matrix, elastomer SEBS and β-crystal nucleating agent are introduced, combined with carbon nanomodified glass fiber (NCGF), and the impact resistance and toughness of the tape are improved through blending and pyrolysis.

Benefits of technology

It significantly improves the impact strength and toughness of glass fiber reinforced tape, and enhances its use stability and safety performance in high-frequency transmission wires and cables.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention relates to a glass fiber reinforced adhesive tape and a preparation method thereof, and relates to the technical field of adhesive tapes, the glass fiber reinforced adhesive tape comprises an aluminum foil layer, an adhesive layer and a release layer, wherein the adhesive layer is prepared from the following components in parts by weight: 400 to 900 parts of polypropylene, 100 to 400 parts of hydrogenated styrene-butadiene block copolymer, 100 to 400 parts of carbon nano modified glass fiber, 1 to 10 parts of beta crystal form nucleating agent, 1 to 3 parts of tackifier and 2 to 5 parts of aging inhibitor. And the heat-conducting property of the glass fiber reinforced adhesive tape is also improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of adhesive tape technology, and in particular to a glass fiber reinforced adhesive tape and its preparation method. Background Technology

[0002] Adhesive tapes are mainly classified according to their different functional characteristics, specifically including: high-temperature tapes, double-sided tapes, insulating tapes, fiber tapes, pressure-sensitive tapes, and die-cut tapes, etc. Each type of tape, due to its unique properties, meets the diverse needs of different industries.

[0003] Currently, commercially available fiberglass tapes mainly improve their performance by adding fiberglass mesh fabric through fiber weaving. Chinese invention patent application CN111777966A, published on October 16, 2020, discloses a fiberglass mesh tape and its preparation method. The fiberglass mesh tape includes a fiberglass mesh fabric layer and an adhesive layer coated on the surface of the fiberglass mesh fabric layer. The adhesive layer is prepared by mixing the following components in parts by weight: 0.5-1.0 parts acrylic acid, 0.3-0.5 parts hydroxyethyl acrylate, 29-32 parts isooctyl acrylate, 9-11 parts butyl acrylate, 7-10 parts vinyl acetate, 47-53 parts ethyl acetate, and 0.2-0.3 parts lauroyl peroxide and 7-9 parts ethyl acetate.

[0004] The addition of glass fiber gives this tape dimensional stability over a very wide temperature range, strong adhesion, high biaxial tensile strength, softness and conformability, abrasion resistance and waterproof and moisture-proof properties, and it can also bond firmly to rough or irregular surfaces.

[0005] Regarding the above-mentioned technical solutions, although this type of fiberglass tape has the characteristics of strong adhesion and dimensional stability, its toughness is generally poor in applications such as computer and peripheral cables, transformer manufacturing, central air conditioning pipelines, water heater pipeline joints, and high-frequency transmission wires and cables, where it may be subject to certain impacts. Under greater force, it is prone to breakage, which reduces the protective effect and safety performance of the tape. Summary of the Invention

[0006] In order to improve the toughness of glass fiber tape, the present invention provides a glass fiber reinforced tape and its preparation method.

[0007] In a first aspect, the glass fiber reinforced tape provided by the present invention adopts the following technical solution: A glass fiber reinforced tape includes an aluminum foil layer, an adhesive layer, and a release layer, wherein the adhesive layer comprises, by weight, 400-900 parts of polypropylene (PP), 100-400 parts of hydrogenated styrene-butadiene block copolymer (SEBS), 100-400 parts of carbon nanotube modified glass fiber (NCGF), 1-10 parts of β-crystal nucleating agent (β-NAs), 1-3 parts of tackifier, and 2-5 parts of aging inhibitor.

[0008] By adopting the above technical solution, polypropylene is used as the matrix, and the elastomer SEBS is introduced. The advantages of each blend component are combined by blending the polymers, while overcoming their own shortcomings, to form a blend PP / SEBS. Compared with pure PP, the impact resistance of PP / SEBS can be greatly improved.

[0009] The addition of β-crystal nucleating agents can induce β-crystalization in PP. In addition to maintaining the good comprehensive performance of α-crystal nucleating agents, the presence of β-crystals in PP can effectively improve the toughness of PP. Its elongation at break and notched impact strength are improved compared with α-crystals, and it can transform α-crystals into β-crystals.

[0010] The addition of glass fiber (GF) to carbon nanofiber modified glass fiber can improve tensile strength. At the same time, a small amount of nano-sized GF and β-NAs act as nucleating agents, while other micron-sized GFs act as fillers and reinforcements, thus increasing the tape's tensile strength and toughness.

[0011] Meanwhile, the NC attached to the GF surface can synergistically interact with SEBS. The SEBS dispersion phase alone is a deformed spherical shape, such as elliptical and rod-shaped droplets. When NC enters the blend of PP and SEBS, the lower interfacial energy between NC and SEBS allows for the selective distribution of NC in the SEBS phase, resulting in a more uniform spherical shape and distribution of the SEBS dispersion phase. At the same time, the SEBS phase containing NC has a higher viscosity, and the increased viscosity ratio between SEBS and PP helps maintain the dispersion morphology of uniform spherical SEBS droplets.

[0012] β-NAs tend to remain in the PP phase. The presence of β-NAs in PP increases the viscosity of PP, reduces the viscosity ratio between SEBS and PP, and facilitates the formation of continuous strip-shaped SEBS phase morphology. When β-NAs and NC coexist in PP / SEBS blends, the resulting SEBS dispersed phase morphology is the result of the combined effect of β-NAs and NC on the PP / SEBS blend. The presence of β-NAs in the PP / SEBS blend transforms the deformed spherical droplets of the SEBS dispersed phase into a locally continuous phase morphology. Further addition of NC results in a better phase morphology, namely a quasi-cocontinuous morphology and tiny spherical droplets distributed in the PP matrix.

[0013] Therefore, an impact energy dissipation stage emerges, where tiny SEBS droplets act as stress concentration points. When an impact force is applied, these stress concentration points transfer the force to the fully contacted PP matrix containing abundant soft β-crystals. Simultaneously, the continuous strip-shaped SEBS phase in the PP matrix deforms into filaments, effectively connecting the stacked PP regions. All these factors work together, and the addition of trace amounts of β-NAs and NCs to the PP / SEBS blend significantly improves the impact strength.

[0014] Optionally, the modified glass fiber is a mixture of modified hollow glass fiber and modified nanoparticle glass fiber.

[0015] By adopting the above technical solution, when hollow glass fibers are carbon-coated, non-metallic minerals (NCs) also adhere to the inner wall of the glass fibers. When added to the blend, the NCs on the outer wall of the glass fibers are peeled off and dispersed into the blend and combine with it. However, due to the small pore size of the glass fibers, the blend does not easily enter, and the NCs on the inner wall remain attached to the inside of the glass fibers, enhancing its thermal conductivity. The addition of nanoparticle glass fibers, compared with GFs of other sizes, acts as a nucleating agent. The presence of β crystals in PP can effectively improve the toughness of PP. Typically, the generation of β crystals in polypropylene includes nucleating agent modification and nanoparticle filling. When β-NAs are used alone, rigidity decreases and toughness increases. For nanoparticle filling modification, the cost is always high, and problems such as agglomeration and uneven mixing are prone to occur during the preparation process. Therefore, nanoparticle GF-reinforced PP can achieve a combination of rigidity and toughness, and the cost is low. The preparation process is easy to achieve continuous operation, which has important application significance for improving the toughness of traditional PP.

[0016] Optionally, the mass ratio of the modified hollow glass fiber to the modified nanoparticle glass fiber is 9-13:1.

[0017] By adopting the above technical solution, the amount of hollow glass fiber and nanoparticle glass fiber used can achieve good thermal conductivity while also having good nucleating agent properties.

[0018] Secondly, the method for preparing glass fiber reinforced tape provided by the present invention adopts the following technical solution: A method for preparing a glass fiber reinforced adhesive tape includes the following steps: 100-400 parts of glass fiber and 5-15 parts of polyethylene (PE) were placed in two different corundum boats, and the two boats were placed side by side in a tube muffle furnace. The tube was heated from room temperature to 700-1000°C at a rate of 10°C / min, and argon gas was pumped into the tube at a rate of 50 mL / min. The pressure was maintained at 1 atm. Then the tube was cooled to room temperature at a rate of 25°C / min to obtain NCGF. SEBS, β-NAs, NCGF, tackifier, aging inhibitor and PP are all physically mixed together, and a blend is prepared using a twin-screw extruder with a screw speed of 25-80 rpm and a melt temperature of 150-200℃ from the hopper to the extruder to obtain an adhesive. The adhesive is applied to the surface of the aluminum foil and cooled to form an adhesive layer; A release layer is applied to the surface of the adhesive layer to obtain a glass fiber reinforced tape.

[0019] By adopting the above technical solution, step (1) grows NCGF on the NC coating by pyrolysis of polyethylene. The coating surface is defect-free, continuous and very smooth. The coating is in complete contact with the surface of the glass fiber. The coating is very thin and its thickness is uniform on the circumference, so that the NC content of the load is more sufficient and the structure is better, and it can be stably fixed on the surface of the glass fiber. The addition of carbon nanoparticles (NC) attached to carbon nanomaterials modified glass fibers allows for initial adsorption, which pulls O atoms from the SiO2 on the GF surface out of the substrate and forms CO by breaking Si-O bonds. This results in significant deoxidation of the SiO2 surface. Subsequent adsorption interacts with the deoxidized SiO2 surface through electron capture, forming stable Si-C bonds, and thus forming a stable SiC layer on the glass fiber surface. This SiC transition thin layer between the SiO2 surface and the carbon coating allows the carbon coating to be firmly bonded to the glass fiber. Furthermore, after sufficient structural relaxation, the carbon layer on the SiC / SiO2 substrate can still maintain the structural characteristics of the carbon layer, giving the coating good thermal conductivity.

[0020] Step (2) involves fully mixing and reacting the various added components through melt blending to form an adhesive; Steps (3-4) involve assembling the various parts into a glass fiber reinforced tape.

[0021] Optionally, the heating temperature of the tubular muffle furnace is 800-900℃.

[0022] By adopting the above technical solution, polyethylene pyrolysis is more thorough at high temperatures, generating more free active carbon atoms, which promotes chemical adsorption and coating growth. At the same time, the temperature is not too high, so it is less likely to damage the glass substrate and affect its performance. Therefore, 800-900℃ is a more suitable temperature for covering glass fiber with carbon coating.

[0023] Optionally, in step (2), the β-NAs and 1% of the total PP mixture are first melt-blended through a micro twin-screw extruder to obtain the desired dispersion. The screw speed is 25 rpm, and the melt temperature from the hopper to the extruder is 150-185℃ to obtain the masterbatch. After granulation, the remaining PP and other components are added to dilute the masterbatch. The screw speed is 80 rpm, and the melt temperature from the hopper to the extruder is 175-200℃ to obtain the adhesive.

[0024] By employing the above technical solution, β-NAs are first dispersed into a portion of polypropylene. At low temperatures, β-NAs remain solid and insoluble in PP. The aggregated particles of solid β-NAs lack mobility. As the temperature increases, β-NAs begin to dissolve and enter a saturated state. Upon cooling, guided by the hydrogen bonds between the amide groups on β-NAs, the dissolved molecules readily crystallize along a preferred direction on the undissolved molecules, forming a needle-like morphology, thus obtaining the masterbatch. The masterbatch is then added to the remaining PP for a diffusion-controlled release process. The growth of β-NAs is influenced by the release rate of β-NAs from the PP carrier. Rate control reduces the effective amount of β-NAs during the growth stage. Reducing the effective amount of β-NAs can limit the dendritic growth of β-NAs to obtain uniform and fine dendritic β-NAs and β crystals. At the same time, as β-NAs completely dissolve to form an unsaturated solution, uniform nucleation and growth will also cause β-NAs to form highly branched dendritic aggregates. By using a stepwise method, β-NAs are selectively enriched in the carrier and then directionally migrated into the polymer matrix to obtain more dendritic crystals. Due to the better connection between dendritic crystals, the impact strength of PP sheets containing dendritic β crystals increases.

[0025] Optionally, the PP is PP with a melt flow index ≥ 4 g / 10 min.

[0026] By adopting the above technical solution, the viscosity of the polymer melt is related to the molecular weight. As the molecular weight of polypropylene decreases, the melt viscosity decreases. Compared with macromolecular solvents, short-chain small molecules do not have long chains and entangled networks, and will not produce a cage effect. The steric hindrance of solute molecules is small, making it easy to diffuse through the boundary layer and eventually dissolve into the melt. The nucleation efficiency of β-NAs increases, making it easy to generate a large number of fine dendritic β crystals. The size of β-NAs decreases, and small-sized β-NAs have a higher specific surface area. Therefore, the nucleation efficiency of β-NAs is improved, making the β crystals more perfect.

[0027] Optionally, the silica content of the glass fiber is ≥ 95.0%.

[0028] By adopting the above technical solution, the higher the silica content in the glass fiber, the more stable Si-C bonds are formed with the subsequent adsorption of active carbon atoms. After the carbon layer is formed, a stable SiC layer will appear, making the NC more stable in the glass fiber.

[0029] Optionally, the polyethylene is linear low-density polyethylene (LLDPE).

[0030] By adopting the above technical solution, LLDPE has a narrow molecular weight distribution and short branches. Because the lack of long branches in LLDPE makes the polymer easier to decompose into NC, it has better decomposition and dispersion performance.

[0031] In summary, the present invention has at least one of the following beneficial technical effects: The combined effect of β-NAs and NC on PP / SEBS blends transforms the deformed spherical droplets of the SEBS dispersed phase into a locally continuous phase morphology due to the presence of β-NAs. Further addition of NC results in an even better phase morphology: a quasi-cocontinuous morphology and tiny spherical droplets distributed within the PP matrix. When an impact force is applied, the stress concentration point transfers the force to the fully contacted PP matrix containing abundant soft β-crystals. Simultaneously, the continuous strip-like SEBS phase in the PP matrix deforms into filaments, effectively connecting the packed PP regions. All these factors work together, and the addition of trace amounts of β-NAs and NC to the PP / SEBS blend significantly improves the impact strength.

[0032] By selecting hollow glass fiber to increase the thermal conductivity of the tape, and using nanoparticle GF to reinforce PP, a combination of rigidity and toughness can be achieved, and the cost is relatively low. This has important application significance for improving the toughness of traditional PP.

[0033] NCGF is obtained by growing NC coating through the pyrolysis of polyethylene. The coating surface is defect-free, continuous and very smooth. The coating is in complete contact with the surface of the glass fiber. The coating is also very thin and its thickness is uniform around the circumference.

[0034] A stepwise method is used to selectively enrich β-NAs in the carrier, and then directionally migrate them to the polymer matrix. A diffusion-controlled release process is carried out to control the release rate of β-NAs from the PP carrier. This reduces the effective amount of β-NAs during the growth stage. Reducing the effective amount of β-NAs can limit the dendritic growth of β-NAs to obtain uniform and fine dendritic β-NAs and β crystals. Due to the better connection between the dendritic crystals, the impact strength of PP sheets containing dendritic β crystals is increased. Detailed Implementation

[0035] The present invention will be further described in detail below with reference to the embodiments.

[0036] In a specific embodiment of the present invention, the tackifier is C5 petroleum resin; the Tg of the C5 petroleum resin is 48°C and the relative molecular weight is 2000.

[0037] In a specific embodiment of the present invention, the aging inhibitor is a primary antioxidant (hindered phenolic oxidant), a secondary antioxidant (phosphite), and a light stabilizer (hindered amine light stabilizer) in a ratio of 1:1:1.

[0038] In a specific embodiment of the present invention, the substrate is aluminum foil with a thickness of 100 μm.

[0039] In a specific embodiment of the present invention, the release film is a silicone release film.

[0040] In a specific embodiment of the present invention, the adhesive coating is 150 μm thick.

[0041] Example 1: This example discloses a glass fiber reinforced tape, the composition of which includes the following by weight: 600 parts of polypropylene (PP), 300 parts of hydrogenated styrene-butadiene block copolymer (SEBS), 200 parts of carbon nanotube modified glass fiber (NCGF), 5 parts of β-crystal nucleating agent (β-NAs), 2 parts of tackifier, and 3 parts of aging inhibitor, wherein the PP is PP with a melt index of 4 g / 10 min.

[0042] Its preparation method is as follows: 200 parts of glass fiber and 10 parts of polyethylene (PE) were placed in two different corundum boats, and the two boats were placed side by side in a tube muffle furnace. The tube was heated from room temperature to 900°C at a rate of 10°C / min, and argon gas was pumped into the tube at a rate of 50 mL / min. The pressure was maintained at 1 atm. Then the tube was cooled to room temperature at a rate of 25°C / min to obtain NCGF. SEBS, β-NAs, NCGF, tackifier, aging inhibitor, and PP were all physically mixed together. The blend was prepared using a twin-screw extruder at a screw speed of 80 rpm, with a melt temperature of 175-200°C from the hopper to the extruder, yielding the adhesive. The adhesive is applied to the surface of the aluminum foil and cooled to form an adhesive layer; A release layer is applied to the surface of the adhesive layer to obtain a glass fiber reinforced tape.

[0043] Example 2: This example discloses a glass fiber reinforced tape, the composition of which includes the following by weight: 600 parts of polypropylene (PP), 300 parts of hydrogenated styrene-butadiene block copolymer (SEBS), 200 parts of carbon nanotube modified glass fiber (NCGF), 5 parts of β-crystal nucleating agent (β-NAs), 2 parts of tackifier, and 3 parts of aging inhibitor, wherein the PP is PP with a melt index of 4 g / 10 min.

[0044] Its preparation method is as follows: 200 parts of glass fiber and 10 parts of polyethylene (PE) were placed in two different corundum boats, and the two boats were placed side by side in a tube muffle furnace. The tube was heated from room temperature to 900°C at a rate of 10°C / min, and argon gas was pumped into the tube at a rate of 50 mL / min. The pressure was maintained at 1 atm. Then the tube was cooled to room temperature at a rate of 25°C / min to obtain NCGF. The mixture of β-NAs and 1% PP is first melt-blended using a micro twin-screw extruder to obtain the desired dispersion. The screw speed is 25 rpm, and the melt temperature from the hopper to the extruder is 150-185℃ to obtain a masterbatch. After granulation, the remaining PP and other components are added to dilute the masterbatch. The screw speed is 80 rpm, and the melt temperature from the hopper to the extruder is 175-200℃ to obtain the adhesive.

[0045] The adhesive is applied to the surface of the aluminum foil and cooled to form an adhesive layer; A release layer is applied to the surface of the adhesive layer to obtain a glass fiber reinforced tape.

[0046] Example 3: This example discloses a glass fiber reinforced tape. Its preparation method is as follows: 200 parts of a mixture of hollow glass fiber and nanoparticle glass fiber in a mass ratio of 11:1 and 10 parts of polyethylene (PE) were placed in two different corundum boats. The two boats were placed side by side in a tube muffle furnace. The tube was heated from room temperature to 900°C at a rate of 10°C / min. Argon gas was pumped into the tube at a rate of 50 mL / min and the pressure was maintained at 1 atm. The tube was then cooled to room temperature at a rate of 25°C / min to obtain NCGF. Everything else is exactly the same as in Example 2.

[0047] Example 4: This example discloses a glass fiber reinforced tape, the composition of which includes the following parts by weight: 600 parts of polypropylene (PP), 300 parts of hydrogenated styrene-butadiene block copolymer (SEBS), 200 parts of carbon nanotube modified glass fiber (NCGF), 5 parts of β-crystal nucleating agent (β-NAs), 2 parts of tackifier, and 3 parts of aging inhibitor, wherein the PP is PP with a melt index of 2.2 g / 10 min.

[0048] Everything else is exactly the same as in Example 2.

[0049] Example 5: This example discloses a glass fiber reinforced tape. Its preparation method is as follows: 200 parts of glass fiber and 10 parts of polyethylene (PE) were placed in two different corundum boats, and the two boats were placed side by side in a tube muffle furnace. The tube was heated from room temperature to 750°C at a rate of 10°C / min, argon gas was pumped into the tube at a rate of 50 mL / min, and the pressure was maintained at 1 atm. Then it was cooled to room temperature at a rate of 25°C / min to obtain NCGF. Everything else is exactly the same as in Example 2.

[0050] Comparative Example 1: This comparative example discloses a glass fiber reinforced tape, the composition of which includes 800 parts by weight of polypropylene (PP), 2 parts of tackifier, and 3 parts of aging inhibitor, wherein the PP is PP with a melt index of 4 g / 10 min.

[0051] Its preparation method is as follows: (1) PP and other components are physically mixed together, and a blend is prepared using a twin-screw extruder with a screw speed of 80 rpm and a melt temperature of 175-200℃ from the hopper to the extruder to obtain an adhesive. (2) Apply adhesive to the surface of aluminum foil and cool it to form an adhesive layer; (3) The release layer is applied to the surface of the adhesive layer to obtain glass fiber reinforced tape.

[0052] Comparative Example 2: This comparative example discloses a glass fiber reinforced tape, the composition of which includes, by weight, 700 parts of polypropylene (PP), 300 parts of hydrogenated styrene-butadiene block copolymer (SEBS), 2 parts of tackifier, and 3 parts of aging inhibitor, wherein the PP is PP with a melt index of 4 g / 10 min.

[0053] Everything else is exactly the same as Comparative Example 1.

[0054] Comparative Example 3: This comparative example discloses a glass fiber reinforced tape, the composition of which includes, by weight, 600 parts of polypropylene (PP), 300 parts of hydrogenated styrene-butadiene block copolymer (SEBS), 200 parts of glass fiber, 5 parts of β-crystal nucleating agent (β-NAs), 2 parts of tackifier, and 3 parts of aging inhibitor, wherein the PP is PP with a melt index of 4 g / 10 min.

[0055] Everything else is exactly the same as Comparative Example 1.

[0056] The glass fiber reinforced tapes prepared in Examples 1, 2, 3, 4, 5, Comparative Examples 1, 2, and 3 were tested and experimented on.

[0057]

[0058] By comparing Comparative Examples 1, 2, and 3, it can be seen that the addition of SEBS in Comparative Example 2 has a toughening effect on the tape, and the tape toughness is improved to some extent. Comparative Example 3 shows that, based on Comparative Example 2, the addition of β-NAs helps to reduce the viscosity ratio between SEBS and PP, making it easier to produce a continuous strip-shaped SEBS phase morphology, resulting in a wider dispersion range of SEBS and further improvement in tape toughness.

[0059] Comparing Comparative Example 3 with Example 1, it can be seen that the addition of carbon nanofiber modified glass fiber allows the NC (carbon nanofiber) attached to the GF surface to synergize with SEBS. The selective distribution of NC in the SEBS phase results in a more uniform spherical morphology and distribution of the SEBS dispersion. Furthermore, when β-NAs and NC coexist in the PP / SEBS blend, the further addition of NC leads to a superior phase morphology, namely a quasi-continuous morphology and tiny spherical droplets distributed within the PP matrix. The combined effect of β-NAs and NC significantly improves the impact strength.

[0060] By comparing Example 2 and Example 1, it can be seen that by changing the synthesis method, the stepwise synthesis selectively enriches β-NAs in the support and then directionally migrates them into the polymer matrix. First, the β-NAs are dissolved in a portion of PP and brought to a saturated state. After cooling, under the guidance of hydrogen bonds between the amide groups on the β-NAs, the dissolved molecules easily crystallize along a preferred direction on the undissolved molecules. Then, they are added to the remaining PP to carry out a diffusion-controlled release process, reducing the effective amount of β-NAs in the growth stage. This can limit the dendritic growth of β-NAs to obtain uniform and fine dendritic β-NAs and β crystals. Due to the better connection between the dendritic crystals, the impact strength of the PP sheet containing dendritic β crystals is increased.

[0061] By comparing Examples 3 and 2, it can be seen that by using a mixture of modified hollow glass fiber and modified nanoparticle glass fiber in a suitable ratio, when the hollow glass fiber is carbon coated, NC will also be attached to the inner wall of the glass fiber. When added to the blend, the NC on the outer wall of the glass fiber will peel off and disperse into the blend and combine with it. However, the pore size of the hollow glass fiber is small, and the blend is not easy to enter. The NC on the inner wall will still be attached to the inside of the glass fiber, enhancing its thermal conductivity. The addition of nanoparticle glass fiber, compared with GF of other sizes, will act as a nucleating agent. The presence of β crystals in PP can effectively improve the toughness of PP.

[0062] By comparing Example 4 and Example 2, it can be seen that by increasing the molecular weight of PP, the PP polymer melt with long chains and entangled networks requires solute molecules to overcome greater steric hindrance in order to diffuse through the boundary layer and eventually dissolve into the melt. It has more intermolecular and intramolecular entanglement, the nucleation efficiency of β-NAs is reduced, and it is extremely difficult for PP to form a large number of fine dendritic β crystals. This has some impact on the toughness of the product, but it is within an acceptable range.

[0063] By comparing Example 5 and Example 2, it can be seen that lowering the temperature of pyrolysis of polyethylene reduces the NC content in the tape system and causes uneven distribution, resulting in a decrease in various properties of the tape, but within an acceptable range.

[0064] The above are all preferred embodiments of the present invention and are not intended to limit the scope of protection of the present invention. Therefore, all equivalent changes made in accordance with the structure, shape and principle of the present invention should be covered within the scope of protection of the present invention.

Claims

1. A glass fiber reinforced tape, comprising an aluminum foil layer, an adhesive layer, and a release layer, characterized in that: The adhesive layer comprises, by weight: 400-900 parts of polypropylene, 100-400 parts of hydrogenated styrene-butadiene block copolymer, 100-400 parts of carbon nano-modified glass fiber, 1-10 parts of beta crystal nucleating agent, 1-3 parts of tackifier, and 2-5 parts of aging inhibitor.

2. A glass fiber reinforced adhesive tape according to claim 1, characterized in that: The modified glass fiber is a mixed glass fiber of modified hollow glass fiber and modified nano-particle glass fiber.

3. A glass fiber reinforced adhesive tape according to claim 2, characterized in that: The mass ratio of the modified hollow glass fiber to the modified nanoparticle glass fiber is 9-13:

1.

4. A method for preparing a glass fiber reinforced adhesive tape as claimed in any one of claims 1 to 3, characterized in that: The following steps are involved: (1) placing 100-400 parts of glass fiber and 5-15 parts of polyethylene in two different corundum boats, respectively, and placing the two boats side by side in a tubular muffle furnace, heating the tube from room temperature to 700-1000° C. at a rate of 10° C. / min, pumping argon into the tube at a rate of 50 ml / min, maintaining the pressure at 1 atmosphere, and then cooling to room temperature at a rate of 25° C. / min to obtain carbon nano-modified glass fiber; (2) physically mixing hydrogenated styrene-butadiene block copolymer, β-crystalline nucleating agent, carbon nano-modified glass fiber, tackifier, aging inhibitor and polypropylene together. The blend is prepared using a twin-screw extruder with a screw speed of 25-80 rpm and a melt temperature of 150-200° C. from the hopper to the extruder to obtain an adhesive; (3) applying an adhesive to the surface of the aluminum foil and cooling the foil to form an adhesive layer; (4) Covering the release layer on the surface of the adhesive layer to obtain a glass fiber reinforced tape.

5. The method for preparing a glass fiber reinforced adhesive tape according to claim 4, characterized in that: The heating temperature of the tubular muffle furnace is 800-900°C.

6. The method for preparing a glass fiber reinforced adhesive tape according to claim 4, characterized in that: In the step (2), the β-crystalline nucleating agent and the PP mixture accounting for 1% of the total amount are first melt-blended through a micro twin-screw extruder to obtain the desired dispersion, the screw speed is 25 rpm, the melt temperature from the hopper to the extruder is 150-185°C, and a masterbatch is obtained. After granulation, the remaining polypropylene and other components are added to dilute the masterbatch, the screw speed is 80 rpm, and the melt temperature from the hopper to the extruder is 175-200°C to obtain an adhesive.

7. The method for preparing a glass fiber reinforced adhesive tape according to claim 4, characterized in that: The polypropylene is a polypropylene with a melt index of ≥4g / 10min.

8. The method for preparing a glass fiber reinforced adhesive tape according to claim 4, characterized in that: The glass fiber has a silica content of ≥ 95.0%.

9. The method for preparing a glass fiber reinforced adhesive tape according to claim 4, characterized in that: The polyethylene is linear low density polyethylene.

Citation Information

Patent Citations

  • Polypropylene / nickel plated glass fiber / titanium dioxide composite material and preparation method thereof

    CN105255011A

  • Special adhesive tape for protective clothing

    CN112852314A

  • Vapor sensor and materials therefor

    US20060292033A1